HIV Diagnoses, Prevalence and Outcomes in Nine Southern States - Reif, Susan (J Community Health, 2014)
A group of nine states in the Southern United States, hereafter referred to as the targeted states, has experienced particularly high HIV diagnosis and case fatality rates. To provide additional information about the HIV burden in this region, we used CDC HIV surveillance data to examine characteristics of individuals diagnosed with HIV in the targeted states (2011), 5-year HIV and AIDS survival, and deaths among persons living with HIV (2010). We used multivariable analyses to explore the influence of residing in the targeted states at diagnosis on deaths among persons living with HIV after adjustment for demographics and transmission risk. In 2011, the targeted states had a higher HIV diagnosis rate (24.5/100,000 population) than the US overall (18.0/100,000) and higher proportions than other regions of individuals diagnosed with HIV who were black, female, younger, and living in suburban and rural areas. Furthermore, the targeted states had lower HIV and AIDS survival proportions (0.85, 0.73, respectively) than the US overall (0.86, 0.77, respectively) and the highest death rate among persons living with HIV of any US region. Regional differences in demographics and transmission risk did not explain the higher death rate among persons living with HIV in the targeted states indicating that other factors contribute to this disparity. Differences in characteristics and outcomes of individuals with HIV in the targeted states are critical to consider when creating strategies to address HIV in the region, as are other factors identified in previous research to be prominent in the region including poverty and stigma.